(untitled) (Revista de Psicología, 2019)
This article presents information about meeting points that certain theories from the Russian psychologist Lev S. Vygotsky and the Chilean biologist Humberto Maturana have. Specifically, it shows their similitude in relation to the following topics: the construction of knowledge as a common topic, a genetic perspective on their works, reconciliation of biological and social actions, and the application of their theories to the discipline of education. Their works and their theories erase the very fine line that traditionally divides their fields of study, and for this they have contributed to the theory and practice of education.